2016
DOI: 10.1016/j.vaccine.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

1,5-Iodonaphthyl azide-inactivated V3526 protects against aerosol challenge with virulent venezuelan equine encephalitis virus

Abstract: Venezuelan equine encephalitis virus (VEEV) is a New World alphavirus. VEEV is highly infectious in aerosolized form and has been identified as a bio-terrorism agent. There is no licensed vaccine for prophylaxis against VEEV. The current IND vaccine is poorly immunogenic and does not protect against an aerosol challenge with virulent VEEV. We have previously shown that VEEV inactivated by 1,5-iodonaphthyl azide (INA) protects against footpad challenge with virulent VEEV. In this study, we inactivated an attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…INA has been shown to inactivate enveloped and non-enveloped viruses, including flaviviruses [17][18][19][20]22]. ZIKV was completely inactivated by INA, including the loss of the infectivity of viral RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…INA has been shown to inactivate enveloped and non-enveloped viruses, including flaviviruses [17][18][19][20]22]. ZIKV was completely inactivated by INA, including the loss of the infectivity of viral RNA.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, serial passage of INA-inactivated ZIKV will need to be performed in neonatal mice to confirm complete inactivation. Reduction in the binding of INA-inactivated viruses with their respective antibodies has been described previously [17][18][19][20]22]. INA binds to the cysteine amino acid residues in proteins [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using encephalomyocarditis virus (EMCV), a positive-sense RNA virus, suggested that INA may inactivate the viral RNA genome by direct binding [133,141]. INA-inactivation of V3526 was also carried out and intramuscular immunization of mice with INA-inactivated V3526 conferred complete protection against an aerosol challenge with TrD [142].…”
Section: Vaccinesmentioning
confidence: 99%
“…This model was used successfully to test antivirals against VeeV (Julander et al, 2008a). Additionally, a VeeV vaccine inactivated with 1,5-iodonaphthyl azide V3526 protects against both footpad and aerosol challenge with virulent VeeV in a mouse model (Gupta et al, 2016).…”
Section: Norwalk Virusmentioning
confidence: 99%